STUDYING PROPERTIES OF DENSE SCHEDULES UNDER CONDITION OF LIMITED NUMBER OF SERVICE UNITS - G. P. Volchkova; V. M. Kotov (Informatika)
There is a conjecture that for any dense schedule in the problem Om||Cmax the makespan is atmost (2− 1/m) times the makespan of the optimal schedule, where “m” is the number of machines. In the paper the conjecture is proved for m ≤ 9 аnd some other special cases.